Calculation of oil volume and simulation of oil injection lubrication for high-speed helical gears based on image recognition technology - HU Bo; CHEN Zan; DONG Jianxiong; SU Jie; YIN Lairong (Jixie chuandong)
ObjectiveAt present, there is a relatively sufficient analysis of oil injection lubrication for spur gears, but there is limited research on the commonly used helical gear oil injection lubrication for high-speed gears, especially in calculating the wind resistance power. Oil injection lubrication is often used for high-speed gears due to the difficulty of lubricants adhering to the tooth surfaces because of their large inertia.MethodsA numerical simulation model of helical gear oil injection lubrication using the volume of fluid (VOF) multi-phase flow model for high-speed gear oil injection lubrication was presented. The gas-liquid two-phase flow under the oil injection lubrication state of helical gears was numerically calculated using the moving mesh method. Calculation was used to obtain the lubricating oil distribution, total gas-liquid pressure, and speed nephogram under gear oil injection lubrication. Combined with the image recognition technology, the average oil volume fraction of the tooth flanks of the oil injection lubrication test and simulation were obtained simultaneously; the correctness of the oil injection lubrication model was verified through comparison. The windage power loss and flow field distribution of the gear pair were studied, and the effects of gear speed and fuel injection speed on the oil film adhesion area, moment of wind resistance, and power loss were analyzed.ResultsThe results indicate that the area of oil film adhesion expands with the increasing injection speed and decreases with the increasing helical gear speed. Additionally, the gear windage power loss mainly increases with the increasing helical gear speed, and slightly increases with the increasing injection speed at low speeds. However, the effect of the injection speed weakens as the gear speed increases.